Hardware-In-The-Loop Simulation Of A Distribution Network With An On-Load Tap Changer Controlled By An Intelligent Electronic Device Via Digital Communication - Jurák, Viktor (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
This paper deals with hardware-in-the-loop simulation of the distribution network, whichis equipped with the on-load tap changer on the HV / MV transformer. This tap changer in the simulationis controlled from a real physical external device - the multi-functional intelligent electronicdevice REX 640 from ABB. This device receives and processes the sampled measured values ofvoltages and currents. Based on these values, an instruction to switch the transformer tap is thengiven back into the simulation. All communication between the simulator and the external device isprovided using the IEC 61850 industrial communication protocol. The paper summarizes both thebenefits of hardware-in-the-loop simulations and the possibilities of using intelligent electronic devicesand data communication in distribution systems.
Keywords: HIL simulation; Real-time simulator; IED; Voltage regulation; SMV; GOOSE